Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/molecules20069703
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Iron Bound Lactoferrin and Nanomedicinal Approaches to Enhance Its Bioactive Functions

Abstract: Lactoferrin (Lf), an iron-binding protein from the transferrin family has been reported to have numerous functions. Even though Lf was first isolated from milk, it is also found in most exocrine secretions and in the secondary granules of neutrophils. Antimicrobial and anti-inflammatory activity reports on lactoferrin identified its significance in host defense against infection and extreme inflammation. Anticarcinogenic reports on lactoferrin make this protein even more valuable. This review is focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 170 publications
(198 reference statements)
0
74
0
6
Order By: Relevance
“…Tests carried out on mandarins with bLfcin and Lf (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) showed a significant protection against Penicillium digitatum at a concentration close to the in vitro MIC value [115]. More recently Baruzzi et al demonstrated the interesting activity of bLfcin in controlling microbial spoilage in ready-to-eat leafy vegetables during cold storage [116].…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Tests carried out on mandarins with bLfcin and Lf (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) showed a significant protection against Penicillium digitatum at a concentration close to the in vitro MIC value [115]. More recently Baruzzi et al demonstrated the interesting activity of bLfcin in controlling microbial spoilage in ready-to-eat leafy vegetables during cold storage [116].…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Lf has been described as modulator of the immune system, particularly regulating the production of proinflammatory cytokines [23]. bLf has shown beneficial effects when tested in patients with cancer [24][25][26], and some studies have shown that Lf can promote wound healing and bone growth [5]. bLf showed an immunostimulant effect in calves [27,28], chickens [29], and fishes [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The alginate coating is not dissolved at lower pH in stomach but dissolve at higher pH (.6) in the intestine and due to mucoadhesive nature of the chitosan the remaining CCo-CPbLf NCs stick to the intestine and pass through due to endocytosis and/or transcytosis. 27 The efficacy of these NCs has already been studied against bacterial infection and cancer. Activity of the loaded Lf protein as well as efficacy has been shown previously by Kanwar et al and was found to be present in blood plasma at a concentration of 1,000 ng/mL after 8 hours postadministration and up to 100 ng/mL at 10 days postadministration, which has been found to be optimum to inhibit any tumor or microbial infection.…”
mentioning
confidence: 99%